Social Gospel in the City: Rev. W. E. Gilroy and Hamilton Clergymen Respond to Labour Issues, 1911–1918 - Turkstra, Melissa (Urban History Review / Revue d'histoire urbaine, 2008)
AbstractThis paper examines clergymen’s response to labour issues in early-twentieth-century Hamilton, Ontario. While the majority of Hamilton clergymen ignored the issue of labour, a small group of ministers, with Congregational minister W. E. Gilroy at the helm, established strong ties with organized labour. These ministers championed labour’s cause both inside and outside the pulpit. In addition to making labour issues a regular subject of their sermons, they organized workingmen’s meetings to discuss social issues, publicly supported and spoke at the meetings of working-class organizations, and positioned themselves on the side of unemployed and striking workers.